CRISPR Technology in Tumor Immunotherapy: Application, limitations, and Improvement Methods - Gao, Shenghan; Miao, Xuru; Liu, Jiaqi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
The CRISPR/Cas system is a natural immune mechanism present in prokaryotes, which protects itself by specifically cutting off viral DNA that invades the bacterial body. Under the research of scientists, CRISPR technology has developed into a powerful tool in tumor immunotherapy. It can reduce the inhibitory effect of tumor microenvironment on T cells and enhance tumor immunity by specifically knocking out genes at immune checkpoints (such as PD-1/CTLA-4) on T cells cultured in vitro. However, CRISPR technology also has significant limitations, with the main limitation being its off-target effect - CRISPR is prone to mistakenly identifying and cutting off genes similar to the target gene sequence, including the normal human genome. Once the off-target effect occurs, it will destroy normal genes other than the target gene and cause irreversible damage. Through research, it has been found that CRISPR combined with other technologies can effectively avoid off target effects and reduce treatment risks. This article elaborates on the specific mechanism of CRISPR technology combined with other technologies to avoid off target effects, and explores potential improvement methods.